2020
DOI: 10.1073/pnas.2004748117
|View full text |Cite
|
Sign up to set email alerts
|

An artificial aquatic polyp that wirelessly attracts, grasps, and releases objects

Abstract: The development of light-responsive materials has captured scientific attention and advanced the development of wirelessly driven terrestrial soft robots. Marine organisms trigger inspiration to expand the paradigm of untethered soft robotics into aqueous environments. However, this expansion toward aquatic soft robots is hampered by the slow response of most light-driven polymers to low light intensities and by the lack of controlled multishape deformations. Herein, we present a surface-anchored artificial aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…If the thermal contribution to the back isomerization of the azobenzene moieties ( cis – trans ) is absent, as water acts as a heat sink, this might result in an overall higher cis ‐isomer population, hence in a larger actuation upon irradiation underwater in comparison with air. [ 22,38,39 ] Drag forces in water were not observed to have a negative influence on the actuation amplitude.…”
Section: Resultsmentioning
confidence: 96%
“…If the thermal contribution to the back isomerization of the azobenzene moieties ( cis – trans ) is absent, as water acts as a heat sink, this might result in an overall higher cis ‐isomer population, hence in a larger actuation upon irradiation underwater in comparison with air. [ 22,38,39 ] Drag forces in water were not observed to have a negative influence on the actuation amplitude.…”
Section: Resultsmentioning
confidence: 96%
“…A very recent study has demonstrated that the integration of two different stimuli‐responsive materials, a flexible magnetic polydimethylsiloxane pillar as the magnetically driven stem and a photoresponsive LCP as the light‐controlled gripper, can be utilized to design the surface‐anchored artificial aquatic coral polyp, to mimic the sophisticated motions of the marine organism in water. [ 74 ] The pseudopolyp stirs to attract suspended targets which is driven by the magnetic fields, and captures or releases the targets under the control of light. These intelligent soft systems with coordinated functions and motions can perform tasks not possible for single‐component devices based on conventional LCPs or other functional materials.…”
Section: Discussionmentioning
confidence: 99%
“…Soft actuators, which are capable of converting external stimuli to the desired shape changes or mechanical movements, can provide safe, comfortable and exible human-machine interaction 1 , and hold great potential in many cutting-edge applications, such as soft robots [2][3][4][5] , arti cial muscles 6-8 , biomimetic propellers [9][10][11][12] and soft grippers [13][14][15] . Various soft actuators driven by different stimuli including magnetic elds 16,17 , electric elds 1,18,19 , temperature 20,21 , humidity 15,22 and light have been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the intensity of free-space light may decrease signi cantly during long-distance transport, especially for the environment with strong absorption and scattering 9,13 . Moreover, for the free-space light-driven actuators to execute locomotion or handle objects, the control light generally needs to intentionally follow the motion of the actuator 1 , which vastly restricts the maneuverability and convenience.…”
Section: Introductionmentioning
confidence: 99%